Comparative Analysis of High Voltage Battery Pack Cells for Electric Vehicle - Sehil, Khaled; Darwish, Mohammed K.; Marouchos, Christos; Jeans, William C. (My University, 2020)
Improving the lifetime of electric vehicles is inevitably required for the widely commercializing. This paper attributes the lithium battery cell (LIB) as an electrical energy storage unit for electrically powered motor vehicles. A comparative analysis for 5 lithium cells from different manufacturers has been investigated and analysed. The comparisons have been prepared for Start Voltage, End Voltage, Current, and the use of active cooling under different test conditions, that includes charging and discharging, with and without cell cooling system.
Keywords: Lithium battery; Cell; Energy Storage